Analisis Strategi Pengembangan Kompetensi Aparatur Sipil Negara dalam Meningkatkan Kinerja Organisasi pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Biak Numfor - Melita Pademme; Hermanu Iriawan; Edyanto Edyanto (Universitas Palangka Raya, 2026)
This study aims to analyze the competency development strategy of the State Civil Apparatus (ASN) in improving organizational performance at the Public Works and Spatial Planning Office (PUPR) of Biak Numfor Regency. This study uses a qualitative research method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The informants consisted of organizational leaders, ASN employees, and related parties within the Biak Numfor Regency PUPR Office. The collected data is analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that the ASN competency development strategy at the Biak Numfor Regency PUPR Office has been implemented through competency needs planning, training, and career development, although the implementation is not yet fully optimal. Organizational performance has shown improvement in terms of quality, quantity, efficiency, and effectiveness, although it still faces several obstacles. Supporting factors for ASN competency development include leadership commitment, budget support, and organizational policies. Meanwhile, the inhibiting factors consist of limited human resources, inadequate infrastructure, and low employee motivation. This study concludes that the development of ASN competencies plays an important role in improving organizational performance.